Manajemen Perpustakaan Untuk Menumbuhkan Minat Membaca Dalam Upaya Menciptakan Prestasi Belajar Di Smp Negeri Muara Batang Empuh Mura - Murniyanto, Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The aim of this research is to describe how to plan, organize, implement and supervise the role of library management to foster interest in reading. This research is motivated by a lack of planning, organizing implementation and supervision. Qualitative field research and research methodology describe library management to foster interest in reading in an effort to create student learning achievement. The research subjects are librarians, teacher councilors, students. Meanwhile, data collection methods include observation, interviews and conclusions. documentation, data analysis techniques including data reduction, data presentation and withdrawal The results of library management have implemented management functions (POAC) Planning, Organizing, Actuating, Controlling. Although there are still several things that need to be improved, such as facilities and infrastructure, human resources, library materials, operational costs and library services to make them even better.